Smile — one of the important elements of face aesthetics (Journal of Face Aesthetics, 2019)
The harmony of the smile depends not only on the dentition, but also on the gum tissue, which excessively exposed can negatively affect aesthetics of the smile. Exposure of a small amount of gum during a smile is acceptable however a smile in which the exposure of the gum is more than 2 mm is considered an aesthetic defect called gummy smile. Among the causes of gingival smile listed are: shortened or hyperactive upper lip muscles (levator labii superioris, levator labii superioris alaeque nasi, zygomatic minor muscles), vertical maxillary excess, extrusion of alveolar ridges, altered passive eruption. In the case of hyperactive upper lip muscles, botulinum toxin can be used — this procedure was used in the described cases, and the effects were assessed using the FotoMedicus system and measurements of gingival exposure. In first case Bocouture botulinum toxin was administered on both sides, 4 units bilaterally in the levator labii superioris muscle and 2 units into levator anguli oris muscle. In total, 12 units were given. During the follow‑up the patient reported the start of the effect from the 5th day after the supply with the maximum effect after 12 days. A 6 mm correction of gummy smile was achieved. In the second case 4 units of botulinum toxin were applicated bilaterally into levator labii superioris alaeque nasi muscle. A 3 mm correction of gummy smile was achieved. The aesthetics of the face in a smile definitely improved in both men.
Keywords: gummy smile; aesthetic medicine; botulinum toxin